2000
DOI: 10.1093/jnci/92.12.1006
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Relationships in U.S. Melanoma-Prone Families With CDKN2A and CDK4 Mutations

Abstract: The recurrent CDKN2A mutations were observed in families with and without pancreatic cancer, which suggests that other factors may be involved in the development of pancreatic cancer. Despite hypothetical differences in the mechanisms of action between CDKN2A and CDK4, clinical factors were indistinguishable between CMM case subjects from CDKN2A versus CDK4 families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 17 publications
5
107
0
Order By: Relevance
“…c.-34G>T, p.R24P, p.M53I, p.P75fs, p.G101W, p.R112_L113insR, p.V126D) have shown that the majority result from single genetic origins, i.e. common founders or ancestors (Gruis et al, 1995a(Gruis et al, , 1995bBorg et al, 1996;Platz et al, 1997;Pollock et al, 1998;Liu et al, 1999;Ciotti et al, 2000;Goldstein et al, 2000Goldstein et al, , 2001Auroy et al, 2001;Hashemi et al, 2001;) rather than mutation hotspots in the CDKN2A gene. To date, only one recurrent mutation has been shown to have multiple origins (c.24_47dup24) (Pollock et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…c.-34G>T, p.R24P, p.M53I, p.P75fs, p.G101W, p.R112_L113insR, p.V126D) have shown that the majority result from single genetic origins, i.e. common founders or ancestors (Gruis et al, 1995a(Gruis et al, , 1995bBorg et al, 1996;Platz et al, 1997;Pollock et al, 1998;Liu et al, 1999;Ciotti et al, 2000;Goldstein et al, 2000Goldstein et al, , 2001Auroy et al, 2001;Hashemi et al, 2001;) rather than mutation hotspots in the CDKN2A gene. To date, only one recurrent mutation has been shown to have multiple origins (c.24_47dup24) (Pollock et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of pancreatic cancer in these families differed significantly (p=0.02); the frequency of pancreatic cancer varied from > 30% in p.G101W, p.P75fs, p.R112_L113insR, and p.V126D families to <10% in p.R24P and p.M53I families (figure 1). Fargnoli et al, 1998;MacKie et al, 1998;Soufir et al, 1998;Holland et al, 1999;Newton-Bishop et al, 1999;Della Torre et al, 2001;Mantelli et al, 2002;Lynch et al, 2002 1α c.78insG Fitzgerald et al, 1996;Flores et al, 1997;MacKie et al, 1998;Monzon et al, 1998;Soufir et al, 1998;Holland et al, 1999; Gruis et al, 1995aGruis et al, , 1995bHolland et al, 1999;Goldstein et al, 2000;Vasen et Hussussian et al, 1994;Whelan et al, 1995;Soufir et al, 1998;Ghiorzo et al, 1999;Holland et al, 1999; Codon numbering for the mutations is taken from table 1. Insertions, deletions, and frameshift mutations are shown at the codon in which the mutation.…”
Section: Methodsmentioning
confidence: 99%
“…Further details about the melanoma patients and their families are provided elsewhere. 3,[18][19][20][21][22][23][24][25] …”
Section: Subjectsmentioning
confidence: 99%
“…INK4a are implicated in pancreatic cancer in familial atypical multiple-mole melanoma syndrome (15) and STK11 mutations in Peutz-Jeghers syndrome (16). Other germ line mutations associated with sporadic incidences of pancreatic cancer include those of the FANCG gene (17).…”
Section: Introductionmentioning
confidence: 99%